Antibakteri Cuka Apel Terhadap Pertumbuhan Bakteri Escherichia coli dan Staphylococcus aureus Secara In Vitro - I Wayan Tanjung Aryasa; Ni Putu Rahayu Artini (Universitas Muhammadiyah Surabaya, 2022)
Vinegar has the chemical name acetic acid derived from the Latin word acetum, acetic acid, ethanoic acid, or vinegar is an organic acid chemical compound that is the most important carboxylic acid in commerce, industry, and laboratories known as a sour taster. and aroma in food. But keep in mind that vinegar can work as a disinfectant. One type of vinegar that we know is apple cider vinegar. Based on the background that has been stated above, the problem formulated in this study is how apple cider vinegar inhibits the growth of Escherichia coli and Staphylococcus aureus bacteria. The analysis of this research is in the form of a quasi-experimental, namely by comparing the inhibitory power of apple cider vinegar and control on the growth of Escherichia coli and Staphylococcus aureus bacteria and post-test only control group design. Based on the results of the research that has been carried out, the results show that the diameter of the inhibition zone formed on Escherichia coli bacteria for foreign apple cider vinegar, Indonesian apple cider vinegar, and local apple cider vinegar is 12.33 ± 0.12 mm, 2.21 ± 0.12 mm and 7.42 ± 0.09 mm. While the diameter of the inhibition zone formed on Staphylococcus aureus bacteria for foreign apple cider vinegar, Indonesian apple cider vinegar, and local apple cider vinegar was 14.56 ± 0.46 mm, 0.00 ± 0.00 mm, and 10.36 ± 0.27 mm. So it can be concluded that apple cider vinegar has antibacterial activity against Escherichia coli and Staphylococcus aureus bacteria.